1997
DOI: 10.1097/00004647-199701000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Sulfoximine, a Glutamine Synthetase Inhibitor, Attenuates Increased Extracellular Potassium Activity during Acute Hyperammonemia

Abstract: Summary: Hyperammonemia causes glutamine accumulation and astrocyte swelling. Inhibition of glutamine synthesis re duces ammonia-induced edema formation and watery swelling in astrocyte processes. Ordinarily, astrocytes tightly control ex tracellular K+ activity [K+le. We tested the hypothesis that acute hyperammonemia interferes with this tight regulation such that [K+le increases and that inhibition of glutamine syn thetase reduces this increase in [K+le. Ion-sensitive microelec trodes were used to measure [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 47 publications
2
35
1
Order By: Relevance
“…Downregulation of Kir4.1/Kir5.1, and Cx43 expression could consequently result in reduction of potassium ion siphoning during HA and cause elevated extracellular potassium levels and water accumulation. Consistent with this hypothesis, an elevated extracellular K + concentration was measured in the parietal cortex of healthy rats made hyperammonemic by ammonium acetate infusion (Sugimoto et al, 1997).…”
Section: Discussionsupporting
confidence: 60%
“…Downregulation of Kir4.1/Kir5.1, and Cx43 expression could consequently result in reduction of potassium ion siphoning during HA and cause elevated extracellular potassium levels and water accumulation. Consistent with this hypothesis, an elevated extracellular K + concentration was measured in the parietal cortex of healthy rats made hyperammonemic by ammonium acetate infusion (Sugimoto et al, 1997).…”
Section: Discussionsupporting
confidence: 60%
“…Alternatively, modifications in the interstitial levels of substances with potential vasoactive effects may occur as a result of glial swelling. Sugimoto et al 23 have shown a marked increase in brain extracellular potassium in hyperammonemic normal rats and have postulated that the uptake of potassium into the end-foot processes may be responsible for alterations in blood flow. 24 The explanation is somewhat unsatisfactory, because in their hands CBF was unchanged despite the marked extracellular potassium increase.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that the administration of methionine sulfoximine (MSO), an inhibitor of GS, 41 decreased the death rate of rats following acute ammonia intoxication. Subsequently, a reduction of cerebral glutamine accumulation by MSO was reported to reverse a number of pathophysiologic and metabolic manifestations of experimentally induced HE, including cerebral edema, 42,43 astrocyte swelling in vivo 44 and in cell culture, 45,46 elevated intracranial pressure, 43 increased cerebral blood flow, 16 enhanced extracellular potassium activity, 47 ammonia-induced reactive oxygen species (ROS) production 11,48 and the MPT. 20,21 MSO also reversed ammonia-induced seizures, 40 defects in glucose utilization, 49 and other cerebral metabolic disorders.…”
Section: Glutamine Is Harmfulmentioning
confidence: 99%